Integrated analysis of gait parameters and gene expression profiles in a murine model of subarachnoid hemorrhage. (9th March 2021) - Zheng, Zhi Yuan; Lu, Gang; Xiong, Zhi Qiang; Leung, Chi Kwan; Su, Xian Wei; Li, Tu; Poon, Wai Sang; Chan, Wai Yee; Wong, George Kwok Chu
Abstract: Gait analysis has been widely used to examine the behavioral presentation of numerous neurological disorders. Thorough murine model evaluation of the subarachnoid hemorrhage (SAH)‐associated gait deficits is missing. This study measures gait deficits using a clinically relevant murine model of SAH to examine associations between gait variability and SAH‐associated gene expressions. A total of 159 dynamic and static gait parameters from the endovascular perforation murine model for simulating clinical human SAH were determined using the CatWalk system. Eighty gait parameters and the mRNA expression levels of 35 of the 88 SAH‐associated genes were differentially regulated in the diseased models. Totals of 42 and 38 gait parameters correlated with the 35 SAH‐associated genes positively and negatively with Pearson's correlation coefficients of >0.7 and <−0.7, respectively. p‐SP1 453 expression in the motor cortex in SAH animal models displays a significant correlation with a subset of gait parameters associated with muscular strength and coordination of limb movements. Our data highlights a strong correlation between gait variability and SAH‐associated gene expression. p‐SP1 453 expression could act as a biomarker to monitor SAH pathological development and a therapeutic target for SAH. Abstract : We examined gait variability using an endovascular perforation murine model of SAH on different postoperation days to reveal strong correlations between gait parameters and the gene expression profiles associated with SAH. Our finding provides a quantitative and reliable assessment of the SAH murine model's motor performance. This approach offers valuable insights into the pathophysiology of the disease and will facilitate the development of treatment strategies using SAH murine models. p‐SP1453 could be a potential biomarker to monitor disease progression or response to therapy.